Cadaveric kidney allotransplantation at Krasnoyarsk Regional Clinical Hospital - V. S. Arutyunyan; A. V. Keosyan; M. A. Firsov; D. P. Evdokimov; M. R. Tsokaev; O. S. Amelchugova; E. V. Lukicheva (Вестник трансплантологии и искусственных органов, 2021)
Objective: to evaluate the early and long-term outcomes of cadaveric kidney allotransplantation (CKAT) based on a retrospective analysis of 71 cases treated at Krasnoyarsk Regional Clinical Hospital (KRCH).Materials and methods. From March 2014 to June 2019, 71 kidney transplants were performed at KRCH – 42 (59.15%) men and 29 (40.85%) women. The age of the patients varied from 20 to 59 years (mean age 39.6 ± 8.14 years). The causes of end-stage chronic kidney disease which subsequently led to CKAT were chronic glomerulonephritis, chronic tubulointerstitial nephritis, hypertensive nephropathy (HN), diabetic nephropathy resulting from type I diabetes (DN), nephropathy of mixed genesis (HN + DN), vesicoureteral reflux, congenital angiodysplasia of the kidneys, and Alport syndrome. The mean number of HLA mismatches was 4.5 ± 0.9.Results. Hospitalization lasted for an average of 34.05 ± 9.56 days. Primary function was observed in 32 (45.08%) patients, while 39 (54.92%) cases had delayed function. Post-transplant complications were noted in 23 (32.39%) patients, of whom 12 (16.9%) had early post-transplant complications, while 15 (21.13%) encountered complications in the late post-transplant period. The most frequently diagnosed were immunological, infectious, and urological complications. Vascular, surgical, oncological, and other complications were less frequent. The annual graft survival rate was 87.3%. Patient survival rate was 95.77%. One (1.4%) and 2 (2.81%) patients died in the early and late post-transplant periods, respectively. Hospital mortality – 1 case (1.4%).Conclusion. Kidney transplantation is the most effective treatment for patients with irreversible chronic kidney disease. About 87.33% of transplants were found to be effective. However, 32.39% of patients had postoperative complications. The vast majority of complications were reversible and were corrected conservatively or surgically. Nevertheless, graft loss occurred in 12.67% of cases. The success of transplantation depends on a number of factors related to both the donor and the recipient, as well as the immunological status and surgical technique. A personalized approach to recipients helps to reduce postoperative complications, prevent nephrotoxicity and rejection reactions.